Is inertial flywheel resistance training superior to gravity-dependent resistance training in improving muscle strength? A systematic review with meta-analyses. Issue 1 (January 2018) - Vicens-Bordas, J.; Esteve, E.; Fort-Vanmeerhaeghe, A.; Bandholm, T.; Thorborg, K.
Abstract: Objective: The primary aim of this systematic review was to determine if inertial flywheel resistance training is superior to gravity-dependent resistance training in improving muscle strength. The secondary aim was to determine whether inertial flywheel resistance training is superior to gravity-dependent resistance training in improving other muscular adaptations. Design: A systematic review with meta-analyses of randomised and non-randomised controlled trials. Methods: We searched MEDLINE, Scopus, SPORTDiscus, Web of Science and Cochrane Central Register of Controlled Trials with no publication date restrictions until November 2016. We performed meta-analyses on randomised and non-randomised controlled trials to determine the standardized mean difference between the effects of inertial flywheel and gravity-dependent resistance training on muscle strength. A total of 76 and 71 participants were included in the primary and secondary analyses, respectively. Results: After systematic review, we included three randomised and four non-randomised controlled trials. In the primary analysis for the primary outcome muscle strength, the pooled results from randomised controlled trials showed no difference (SMD = −0.05; 95%CI −0.51 to 0.40; p = 0.82; I 2  = 0%). In the secondary analyses of the primary outcome, the pooled results from non-randomised controlled trials showed no difference (SMD = 0.02; 95%CI −0.45 to 0.49; p = 0.93; I 2  = 0%; and SMD = 0.03; 95%CI −0.43 to 0.50; p = 0.88; I 2  = 0%). Meta-analysis on secondary outcomes could not be performed. Conclusion: Based on the available data, inertial flywheel resistance training was not superior to gravity-dependent resistance training in enhancing muscle strength. Data for other strength variables and other muscular adaptations was insufficient to draw firm conclusions from.